2009
DOI: 10.1128/jvi.01238-09
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Mutations in a Human Immunodeficiency Virus Type 1 Envelope Protein with a Truncated V3 Loop Restore Function by Improving Interactions with CD4

Abstract: We previously reported that a human immunodeficiency virus type 1 (HIV-1) clade B envelope protein with a severely truncated V3 loop regained function after passage in tissue culture. The adapted virus, termed TA1, retained the V3 truncation, was exquisitely sensitive to neutralization by the CD4 binding site monoclonal antibody b12 and by HIV-positive human sera, used CCR5 to enter cells, and was completely resistant to small molecule CCR5 antagonists. To examine the mechanistic basis for these properties, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 71 publications
1
30
1
Order By: Relevance
“…We have automated the complex computational analysis required to derive the sensitivity vector metrics on a Web-based platform (http://versa.biomath.ucla.edu) so that anyone using our Affinofile cells can obtain the vector metrics by imputing the raw infectivity data as described above. In an accompanying study, Doms and colleagues used our Affinofile cells and VERSA, in part, to show that a V3 loop-truncated R5 virus envelope compensated for its inefficient usage of CCR5 by increasing its ability to use low levels of CD4 (1). Not only is our system a valuable tool for better understanding the relationship between viral pathogenesis and the efficiency of CD4/ CCR5 usage, but the application of sensitivity vector analysis to clinical isolates may have implications for guiding entry inhibitor use.…”
Section: Discussionmentioning
confidence: 99%
“…We have automated the complex computational analysis required to derive the sensitivity vector metrics on a Web-based platform (http://versa.biomath.ucla.edu) so that anyone using our Affinofile cells can obtain the vector metrics by imputing the raw infectivity data as described above. In an accompanying study, Doms and colleagues used our Affinofile cells and VERSA, in part, to show that a V3 loop-truncated R5 virus envelope compensated for its inefficient usage of CCR5 by increasing its ability to use low levels of CD4 (1). Not only is our system a valuable tool for better understanding the relationship between viral pathogenesis and the efficiency of CD4/ CCR5 usage, but the application of sensitivity vector analysis to clinical isolates may have implications for guiding entry inhibitor use.…”
Section: Discussionmentioning
confidence: 99%
“…One factor that has been identified as contributing to the magnitude of CCR5 antagonist resistance is the level of CCR5 expression. 41,42 FACS analysis revealed that U87=CD4=CCR5 cells express much lower levels of CCR5 than either NP2=CD4=CCR5 or 293=CD4=CCR5 cells (CCR5 geometric mean fluorescence: 99 vs. 1048 and 1037, respectively). CD4 levels were similar between the three cell lines and did not correlate with the degree of resistance to APL.…”
Section: Resistant Envs Demonstrate Incomplete Inhibition By Aplmentioning
confidence: 99%
“…HIV-1 resistance to such inhibitors is likely to entail unique escape mechanisms given that a host receptor, not a viral enzyme, is the drug target. Potential pathways of resistance to these inhibitors include coreceptor switching to CXCR4-using viruses (16), increased affinity and binding to CD4 and/or CCR5 (17,18), use of inhibitorbound conformations of CCR5 (19,20), and increased kinetics of membrane fusion (21). Although outgrowth of CXCR4-using virus remains a concern for the therapeutic administration of CCR5 antagonists and is why patients are screened for X4-tropic virus prior to starting a maraviroc regimen, de novo mutations altering coreceptor tropism do not appear to be the preferential pathway for resistance (22,23).…”
mentioning
confidence: 99%